Premenstrual symptoms in young adults born preterm at very low birth weight - from the Helsinki Study of Very Low Birth Weight Adults - Pesonen Anu-Katriina; Räikkönen Katri; Vääräsmäki Marja; Halbreich Uriel; Hovi Petteri; Sipola-Leppänen Marika; Mustaniemi Sanna; Heinonen Kati; Järvenpää Anna-Liisa; Eriksson Johan G; Andersson Sture; Kajantie Eero (BMC, 2011)
Abstract Background Clinically significant premenstrual symptoms are common among young women. Premenstrual syndrome (PMS) is characterized by emotional, behavioural and physical symptoms that consistently occur during the luteal phase of the menstrual cycle. Premenstrual dysphoric disorder (PMDD) is a severe form of PMS. Individual variation in stress responsiveness may be involved in the pathophysiology of premenstrual symptoms. Preterm birth at very low birth weight (VLBW, < 1500g) has a multitude of consequences that extend to adult life, including altered stress responsiveness which could affect the prevalence of premenstrual symptoms. Methods In this cohort study, we compared 75 VLBW women with 95 women born at term (mean age 22.5). We used a standardized retrospective questionnaire assessing the presence and severity of a variety of symptoms before and after menses. The symptom scores were used both as continuous and as dichotomized variables, with cutoffs based on DSM-IV criteria for PMDD and ACOG criteria for PMS, except prospective daily ratings could not be used. We used multiple linear and logistic regression to adjust for confounders. Results There was no difference in the continuous symptom score before menses (mean difference VLBW-term -18.3%, 95% confidence interval -37.9 to 7.5%) or after menses. The prevalence of premenstrual symptoms causing severe impairment to daily life was 13.3% for VLBW women and 14.7% for control women. For PMDD, it was 8.0% and 4.2%, and for PMS, 12.0% and 11.6%, respectively. These differences were not statistically significant (p > 0.1). Conclusion Our findings suggest that the severity of premenstrual symptoms and the prevalence of PMDD and PMS among young women born preterm at VLBW is not higher than among those born at term.